2020
DOI: 10.1136/bmjopen-2019-031927
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cerebrovascular event reoccurrence in patients with depression: a retrospective cohort study

Abstract: ObjectivesTo identify predictors of recurrent cerebrovascular morbidity in a cohort of patients with depression and a cerebrovascular disease (CBVD) history.MethodsWe used the Maudsley Biomedical Research Centre Case Register to identify patients aged 50 years or older with a diagnosis of depressive disorder between 2008 and 2017 and a previous history of hospitalised CBVD. Using depression diagnosis as the index date we followed patients until first hospitalised CBVD recurrence or death due to CBVD. Sociodemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, this method only analyzes the characteristics after the early onset of the disease, which has some limitations. Reference [ 12 ] took patients with depression and cerebrovascular diseases as the research object and used the diagnosis of depression as the index date to track and record the recurrence of cerebrovascular diseases. The results showed that the risk of cerebrovascular diseases recurrence mainly depends on age and physical health but had little relationship with depression and psychotropic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method only analyzes the characteristics after the early onset of the disease, which has some limitations. Reference [ 12 ] took patients with depression and cerebrovascular diseases as the research object and used the diagnosis of depression as the index date to track and record the recurrence of cerebrovascular diseases. The results showed that the risk of cerebrovascular diseases recurrence mainly depends on age and physical health but had little relationship with depression and psychotropic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…17 Although it has been shown that precision and recall are relatively high for the medication natural language processing application, 17 there remains a risk underestimating or overestimating the true prescribing prevalence, especially as adherence to medication cannot be established. 53 Lastly, although we incorporated a wide range of potential confounders in our analysis, causal inferences cannot readily be drawn in an observational study of this nature.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The activated HPA axis promoted a “systemic anti-inflammatory response” that negatively affects function recovery and anxiety generation ( 31 ). Besides, anxiety and depression are recognized to be associated with dysregulation of the HPA axis, which accentuates inflammation, consequently increasing the risk of stroke recurrence ( 32 ). Dysfunction of the HPA axis is suspected to be one of the main mechanisms connecting stroke with anxiety ( 33 ).…”
Section: Introductionmentioning
confidence: 99%